Direct visualization of magnetic-field-induced magnetoelectric switching in multiferroic aurivillius phase thin films - Faraz,A; Maity,T; Schmidt,M; Deepak,N; Roy,S; Pemble,ME; Whatmore,RW; Keeney,L (JOURNAL OF THE AMERICAN CERAMIC SOCIETY, 2016)
Multiferroic materials displaying coupled ferroelectric and ferromagnetic order parameters could provide a means for data storage whereby bits could be written electrically and read magnetically, or vice versa. Thin films of Aurivillius phase Bi6Ti2.8Fe1.52Mn0.68O18, previously prepared by a chemical solution deposition (CSD) technique, are multiferroics demonstrating magnetoelectric coupling at room temperature. Here, we demonstrate the growth of a similar composition, Bi6Ti2.99Fe1.46Mn0.55O18, via the liquid injection chemical vapor deposition technique. High-resolution magnetic measurements reveal a considerably higher in-plane ferromagnetic signature than CSD grown films (MS=24.25 emu/g (215 emu/cm3), MR=9.916 emu/g (81.5 emu/cm3), HC=170 Oe). A statistical analysis of the results from a thorough microstructural examination of the samples, allows us to conclude that the ferromagnetic signature can be attributed to the Aurivillius phase, with a confidence level of 99.95%. In addition, we report the direct piezoresponse force microscopy visualization of ferroelectric switching while going through a full in-plane magnetic field cycle, where increased volumes (8.6% to 14% compared with 4% to 7% for the CSD-grown films) of the film engage in magnetoelectric coupling and demonstrate both irreversible and reversible magnetoelectric domain switching.